CCR2-V64IPolymorphism in Multidrug-Resistant TuberculosisPatients in Dr. Moewardi General Hospital in Surakarta - Monica, Windhy; Prasetyo, Afiono Agung; ., Marwoto (Nexus Biomedika, 2015)
Background: Genetic variants of CCR2 (CC chemokine receptor type 2) are associated with susceptibility to tuberculosis (TB), however its association with Multidrug-Resistant Tuberculosis (MDR-TB) is still unknown. The aim of the present study was to find out the status of CCR2-V64I polymorphisms among MDR-TB patients in Dr. Moewardi General Hospital in Surakarta. Methods: Blood samples from 36 MDR-TB patients in Dr. Moewardi General Hospital in Surakarta were subjected to DNA isolation. The DNA was genotyped for CCR2-V64I polymorphisms by a polymerase chain reaction with sequence-specific primers (PCR-SSP). Results: The wild type (GG) was found in 21/36 (58%) samples. The heterozygous genotype (GA), homozygous genotype (AA), and A allele frequencies in the population respectively were 39%, 3%, and 22%. Conclusion: The frequency of mutant type (GA and AA) was found lower than the wild type (GG) in the population of MDR-TB patients. Keywords: CCR2-V64I, MDR-TB, Surakarta